Tau Truncation is a Productive Posttranslational Modification of Neurofibrillary Degeneration in Alzheimer's Disease - Kovacech, B.; Novak, M. (Current Alzheimer Research, 2010)
Deposits of the misfolded neuronal protein tau are major hallmarks of neurodegeneration in Alzheimer's disease (AD) and other tauopathies. The etiology of the transformation process of the intrinsically disordered soluble protein tau into the insoluble misordered aggregate has attracted much attention. Tau undergoes multiple modifications in AD, most notably hyperphosphorylation and truncation. Hyperphosphorylation is widely regarded as the hottest candidate for the inducer of the neurofibrillary pathology. However, the true nature of the impetus that initiates the whole process in the human brains remains unknown. In AD, several site-specific tau cleavages were identified and became connected to the progression of the disease. In addition, western blot analyses of tau species in AD brains reveal multitudes of various truncated forms. In this review we summarize evidence showing that tau truncation alone is sufficient to induce the complete cascade of neurofibrillary pathology, including hyperphosphorylation and accumulation of misfolded insoluble forms of tau. Therefore, proteolytical abnormalities in the stressed neurons and production of aberrant tau cleavage products deserve closer attention and should be considered as early therapeutic targets for Alzheimer's disease. /P>
Keywords: tau transition